Neoliberal governmentality in global English textbooks. Issue 2 (2nd April 2020) - Bori, Pau
ABSTRACT: The purpose of this paper is to contribute to the growing body of literature critically analysing the relation between neoliberalism and the global English Language Teaching (ELT) textbook with a new perspective. In this study, neoliberalism is regarded not only as an economic policy paradigm, but especially in a Foucauldian way, as a form of governmentality, with its emphasis on the responsibilisation of the self and the creation of a certain kind of subjectivity, related to the entrepreneurial-consumerist concept of society. The paper examines two best-selling global UK-produced English language textbooks. I develop a qualitative content analysis to explore in which way and to what extent these textbooks reflect, legitimate and reproduce neoliberal governmentality. The findings of the analysis suggest that the global ELT textbook not only presents a particular neoliberal worldview as common sense, but also encourages students to implement techniques of self-government to become entrepreneurial individuals and responsible consumers. In light of that, the paper concludes by arguing that the global ELT textbook may be regarded as a tool to extend and support the expansion of neoliberal governmentality in today's society.